2006
DOI: 10.1143/jjap.45.5144
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Electrochemical Properties of ZrO2·Hx Thin Films Deposited by Reactive Sputtering in Hydrogen Atmosphere as Solid Electrolytes

Abstract: The feasibility of applying ZrO 2 . H x thin films as solid electrolytes in solid-state ionic energy systems, such as solid oxide fuel cells and supercapacitors was studied. ZrO 2 . H x thin films were deposited on Pt/Ti/SiO 2 /Si substrates by radio-frequency reactive sputtering with various hydrogen volume fractions in reactive gas. With a variation in hydrogen volume fraction, the surface roughness of the as-deposited films increased. In addition, the structure of the as-deposited films grew in the [111] … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…21 At around 160 °C, the conductivity attains a value of 10 −7 S cm −1 , which fully meets the service conditions of inorganic solid ECDs. 22 However, when the temperature is decreased to 25 °C, the conductivity of the sample has been unable to be measured from the Nersten curve (Figure S2, Supporting Information), indicating that the room temperature conductivity of this material is very poor. Therefore, this type of material has the following features: at room temperature, this material is nonconductive, but as the temperature increases, the conductivity increases.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…21 At around 160 °C, the conductivity attains a value of 10 −7 S cm −1 , which fully meets the service conditions of inorganic solid ECDs. 22 However, when the temperature is decreased to 25 °C, the conductivity of the sample has been unable to be measured from the Nersten curve (Figure S2, Supporting Information), indicating that the room temperature conductivity of this material is very poor. Therefore, this type of material has the following features: at room temperature, this material is nonconductive, but as the temperature increases, the conductivity increases.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…14) are thought to be caused by the lower H 2 O content in our films, as described above. The ion conductivity was maintained high even after heat treatment at 200 C, however, it began to decrease after heat treatment above 250 C. Even though some of H 2 O molecules are desorbed from the film during heat treatment, H 2 O molecules are absorbed by the films again at room temperature, owing to the low film density and porous structure of the ZrO 2…”
mentioning
confidence: 79%
“…12) Ion conductivities of hydrated ZrO 2 have been investigated, and England et al 13) reported an ion conductivity of 2 Â 10 À5 S/cm at room temperature for ZrO 2Á 1.75H 2 O powder prepared by a sol-gel technique. Kim et al 14) reported a room-temperature ion conductivity of 1:67 Â 10 À6 S/cm for ZrO 2Á H x thin films with x ¼ 1:70, deposited by reactive sputtering in Ar þ H 2 þ O 2 atmosphere. Furthermore, ZrO 2 solid electrolyte thin films have been successfully applied to all-solid-state electrochromic devices 14,15) and switchable mirrors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5][6] Hydrogen-containing tantalum oxide and zirconium oxide are considered to be candidate proton conducting solid electrolytes, and some of their previously reported data are shown in Table I. [7][8][9][10][11][12] Although the proton conductivities of the sputtered films were relatively lower than those of the films prepared by ion plating and sol-gel techniques, the sputtering technique is considered to be suitable for forming large-area thin films with uniform thickness and quality. Our group has developed a new reactive sputtering technique using H 2 O as a reactive gas and applied the technique to deposit hydrated Ta 2 O 5 and ZrO 2 thin films.…”
mentioning
confidence: 99%